2020
DOI: 10.1126/sciadv.aaz0517
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin enhances visual processing and perception by suppressing excitatory inputs to parvalbumin-positive interneurons in V1

Abstract: Somatostatin (SST) is a neuropeptide expressed in a major subtype of GABAergic interneurons in the cortex. Despite abundant expression of SST and its receptors, their modulatory function in cortical processing remains unclear. Here, we found that SST application in the primary visual cortex (V1) improves visual discrimination in freely moving mice and enhances orientation selectivity of V1 neurons. We also found that SST reduced excitatory synaptic transmission to parvalbumin-positive (PV+) fast-spiking intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 40 publications
1
33
0
Order By: Relevance
“…We showed that TMT-Opsin1b affects the production of sst1b . A member of the somatostatin/corticostatin family in the mouse (SST, active form SST-14) has been shown to itself suppress excitatory inputs to downstream interneurons, resulting in enhanced visual gain and orientation selectivity [ 58 ]. It might hence be plausible to assume that tectal sst1b also exerts suppressive effects.…”
Section: Discussionmentioning
confidence: 99%
“…We showed that TMT-Opsin1b affects the production of sst1b . A member of the somatostatin/corticostatin family in the mouse (SST, active form SST-14) has been shown to itself suppress excitatory inputs to downstream interneurons, resulting in enhanced visual gain and orientation selectivity [ 58 ]. It might hence be plausible to assume that tectal sst1b also exerts suppressive effects.…”
Section: Discussionmentioning
confidence: 99%
“…In mice, administration of an SSTR2 agonist to the main olfactory bulb enhanced olfactory discrimination 26 . In addition, a recent study showed that SST enhanced visual processing in the VISp 27 . This study demonstrated that SST reduced excitatory inputs to the PV + INs and improved visual gain in regular-spiking PNs.…”
Section: Functional Roles Of the Neuropeptide Sst And Its Receptorsmentioning
confidence: 99%
“…where, Cmem and g l are the membrane capacitance and leak conductance per unit area, u l is the leak reverse potential, and I Ca is the active dendritic feedback. We model in-vivo-like external input per unit area , Iext, by a generic white-noise process as Iext = µ + ση(t) [21] where, µ and σ are the mean and standard deviation of the process, and η(t) is a Gaussian white noise variable, where η(t) = 0 and η(t)η(t ) = δ(t − t ). We use the notation of .…”
Section: The Emergence Of Meta-stability In the Slow-fast Analysismentioning
confidence: 99%